2021
DOI: 10.1101/2021.01.30.428778
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive molecular features of polycystic ovary syndrome revealed by transcriptome analysis of oocytes and cumulus cells

Abstract: PCOS is typically characterized by polycystic ovarian morphology, hyperandrogenism, ovulatory dysfunction and infertility. Furthermore, PCOS patients undergoing ovarian stimulation have more oocytes, however, poor quality of oocytes lead to lower fertilization and implantation rates, decreased pregnancy and increased miscarriage rates. Our study suggests that global gene expression and cell to cell interactions of oocytes and CCs are significantly altered in women with PCOS. Noticeably, genes related to microt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 87 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Tuba1c, along with Tubb8, is over-expressed in PCOS oocytes where the MTs are defective along with general spindle defects potentially resulting in low-quality oocytes (Li et al, 2021). It was previously shown that Tubb8 is the predominant β-tubulin that is expressed only in primate oocytes and TUBB8 mutations result in oocyte maturation arrest, thereby resulting in female infertility .…”
Section: Tuba1cmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuba1c, along with Tubb8, is over-expressed in PCOS oocytes where the MTs are defective along with general spindle defects potentially resulting in low-quality oocytes (Li et al, 2021). It was previously shown that Tubb8 is the predominant β-tubulin that is expressed only in primate oocytes and TUBB8 mutations result in oocyte maturation arrest, thereby resulting in female infertility .…”
Section: Tuba1cmentioning
confidence: 99%
“…Even though Tubb8 is also expressed in spermatozoa, the mutations do not render males infertile, but instead, the next female generation inherits infertility associated with the mutated copy of TUBB8 following the Mendelian pattern of inheritance . Recently, significant overexpression of Tubb8 has been seen in PCOS oocytes with defective MTs along with general spindle defects leading to overall low-quality oocytes (Li et al, 2021). TUBB8 mutations associated with female infertility are very commonly observed and there are more that 120 variants reported till date in infertile females (Appendix Table.…”
Section: Tubb8mentioning
confidence: 99%